The application of nano-crystalline PbO2 as an anode for the simultaneous bio-electrochemical denitrification and organic matter removal in an up-flow undivided reactor - Mook, W.T.; Aroua, M.K.; Chakrabarti, M.H.; Low, C.T.J.; Aravind, P.V.; Brandon, N.P. (Elsevier, 2013)
A nano-crystalline PbO2 coated carbon composite has been applied as an anode for an up-flow undivided bio-electrochemical reactor (UBER). This electrode provides an enhanced destruction of organic matter in synthetic wastewater in comparison to other anodic materials such as stainless steel, graphite and carbon felts or titanium. The cathode is a granular activated carbon coated with a film of autohydrogenotrophic bacteria. Denitrification occurs simultaneously at the cathode while organic matter is oxidized at the anode. Optimum conditions for the simultaneous removal of organic matter and nitrate from response surface methodology (RSM) studies are an inter-electrode spacing of 3.2 cm, electric current of 18 mA and HRT of 45 h that gave organic matter removal efficiencies of 83 along with 99 removal of nitrate. Further studies on the mechanisms of denitrification and organic matter removal are envisaged.